A new critically endangered species of Bertolonia (Melastomataceae, Bertolonieae) from Espírito Santo, Brazil - Bacci, Lucas F.; Iglesias, Diego Tavares; Goldenberg, Renato (Phytotaxa, 2020)
We describe here Bertolonia lucernula, a new endemic species from the state of Espírito Santo, Brazil. It is only known from one locality, the “Área de Proteção Ambiental Mestre Álvaro”, in the municipality of Serra. The new species can be recognized by the branches and petioles covered with sessile and short-stalked glands and scattered unbranched trichomes, flat leaf blade surfaces covered only with sessile and short-stalked glands, small flowers with a widely campanulate hypanthium covered with the same trichomes as the petioles, calyx with membranaceous, truncate sepals, and short, triangular external teeth, asymmetric and obovate petals, with the apex covered with sessile and short-stalked glands on the adaxial surface. According to IUCN criteria, Bertolonia lucernula should be classified as Critically Endangered (CR).